THE CORRELATION BETWEEN STUDENTS' WRITING ATTITUDE AND THEIR WRITING ACHIEVEMENT AMONG TWELFTH GRADERS - Hamidah, Nurul; Ayu, Mutiara (LPPM Univ. Ibn Khaldun Bogor, 2025)
This study aims to investigate the correlation between students’ writing attitudes and their writing achievement among twelfth-grade students at SMA Tri Sukses Natar. Writing is considered one of the most essential skills in English as a Foreign Language (EFL) learning since it reflects students’ critical thinking ability, language competence, and confidence in expressing ideas in written form. This research employed a quantitative correlational design involving 23 twelfth-grade science students. The data were collected through a writing attitude questionnaire and a writing achievement test in the form of a descriptive essay consisting of 200–250 words. The data were analyzed using SPSS version 21 with the Pearson Product-Moment Correlation formula to determine the relationship between the two variables. The results showed that the students’ mean score of writing attitude was 2.87, indicating a neutral to positive attitude, while the mean score of their writing achievement was 55.91, which falls into the “fair” category. The correlation result showed that r = -0.131, indicating a very weak and negative correlation, which is statistically insignificant. This finding suggests that students’ positive attitudes toward writing do not necessarily translate into higher writing performance. It implies that other factors, such as motivation, language proficiency, and writing practice, may play a more influential role. Therefore, teachers are encouraged to foster students’ enthusiasm for writing by providing constructive feedback, creating an enjoyable learning atmosphere, and giving more opportunities for authentic writing practice.